Why Investing in Diversity Management Matters: Organizational Attraction and Person–Organization Fit. (August 2018) - Madera, Juan M.; Dawson, Mary; Neal, Jack A.
Corporate investments in diversity management programs have increased over the past two decades. Across two samples, the current study used experimental methods to examine if organizational attraction and person–organization fit (P–O fit) are influenced by corporate investment in diversity management. In Study 1, 132 hotel managers read about a hotel company that either invested in diversity management programs or removed their investment. In Study 2, 159 hospitality students on the job market read about a hotel company that either invested in diversity management programs or did not read this statement. The results of the current study showed why investing in diversity management matters, namely, because investing in diversity management influences organizational attraction. Across two studies, the participants were more attracted to an organization if the organization invested in diversity management and P–O fit mediated the relationship between corporate investment in diversity management and organizational attraction.